Historyk literatury i jego przyszłość. (Auto)refleksje - Partyka, Magdalena (Colloquia Litteraria, 2018)
The article shows the situation of literary historians, their social role and tasks in the contemporary literary theory. The author presents opinions on the discipline expressed by such experienced researchers as Kazimierz Wyka, Teresa Kostkiewiczowa, Włodzimierz Bolecki, and she askes how the students of literary studies perceive the history of literature. She writes about difficulties, dilemmas and quandaries associated with the work of contemporary literature researchers who are interested in old literature. She shows some examples of studies where historical imagery has become a foundation for the creation of numerous associations combining antiquity and modernity, where it allowed to see the polar character of references and follow-ups, as well as to describe the variability of creative endeavors and realisations in literature, and finally to reveal moments of coexistence of dichotomous phenomena. The author presents the dramaturgy of work of literary historians’ who are entangled in multilevel determinants of the historical world, which they investigate, and the present one, which they experience.